2001
DOI: 10.1507/endocrj.48.345
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentration of Androstenediol and Androstenediol Sulfate in Patients with Hyperthyroidism and Hypothyroidism.

Abstract: Abstract.Androstenediol (5-androsten-3 j3, 17~-diol, ADIOL) and androstenediol 3-sulfate (ADIOLS) are active metabolites of dehydroepiandrosterone (DHEA) and DHEA sulfate (DHEAS), respectively, and have estrogenic activity and immunoregulatory function.We examined serum concentrations of ADIOL, ADIOLS, DHEA, DHEAS and pregnenolone sulfate (5-pregnen-3j3-o1-20-one sulfate, PREGS) in patients with Graves' thyrotoxicosis (male/female 9/14), hypothyroidism (11/20) and in normal controls (14/29). In hypothyroidism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 44 publications
2
21
0
2
Order By: Relevance
“…However, in hypothyroid males, testosterone and free testosterone are low and estradiol levels are normal (18,24) and have no apparent impact on gonadotrophin secretion because there is no reciprocal increase in FSH and LH. In sheep and rats, inhibin B suppresses FSH synthesis and secretion (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, in hypothyroid males, testosterone and free testosterone are low and estradiol levels are normal (18,24) and have no apparent impact on gonadotrophin secretion because there is no reciprocal increase in FSH and LH. In sheep and rats, inhibin B suppresses FSH synthesis and secretion (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, we injected decreasing amounts of the derivative and found that at Ͻ500 pg the signal-to-noise ratio was already Ͻ3. On this basis, we assume that interference after processing of a serum sample containing physiologic concentrations of (3␤,17␤)-androst-5-ene-3,17-diol would be very unlikely (32 ).…”
Section: Results and Discussion Uf-id-gc/ms Candidate Rmpmentioning
confidence: 99%
“…The exaggerated T response to hCG also underlines the role of hypothalamic-pituitary unit rather than a primary testicular effect. A decrease has also been shown in DHEA, DHEAS, andostendiol and pregnenolone sulfate (Tagawa et al, 2001). The endocrine dysfunction partially explain the sexual symptoms complained in such patients, such as decreased libido or erectile dysfunction (Carani et al, 2005;.…”
Section: Hypothyroidism and Male Infertilitymentioning
confidence: 89%